Epidemiology and preventive direction of periodontology in China - Qin-Tao Wang (Blackwell Synergy, 2007)
Objective: The aim of this work was to estimate the present periodontal problems of people in China, based on an epidemiological investigation of adults. Material and Methods: The data were collected from the northwest, southwest, northeast and east regions (400 subjects from each region) of China. All subjects were over 25 years of age. About half of the subjects were farmers and about half were urban professionals. Everyone was asked to fill out a questionnaire and to undergo a professional oral examination. Periodontal health status was evaluated by a simplified oral hygiene index (OHI-S), gingival index (GI), bleeding on probing (BOP), probing pocket depth (PD), clinical attachment loss (CAL), and tooth mobility. Results: Of the 1590 subjects enrolled in this investigation, 45.7% were male, 45.5% were farmers, and the remaining were urban professionals, and 27.7% of the subjects were smokers. There was a significant difference in the educational background but not smoking between the rural and urban groups. While 34.9% of the subjects in the urban group brushed only once per day, 56.1% of the subjects in the rural group did so. The prevalence of bleeding during brushing was 71.1%, while about 61.4% of the subjects know nothing about scaling. All periodontal indices were significantly higher in males than in females and higher in the rural group than in the urban group. PD, CAL and tooth mobility increased with age. The percentage of sites with CAL43mm in the rural group (49.5%) was significantly higher than that in the urban group (37.5%). Both current and former smokers showed increased CAL than non-smokers. Conclusion: Gingivitis and periodontitis are common findings in China. Most Chinese have no knowledge of common periodontal prevention and treatment and very few have regular dental care. The data of this study suggest that age, smoking, and limited education are significantly associated with Chinese adult periodontal attachment loss. Preventive periodontal care and education should be reinforced in the future by establishing relevant oral health projects.